The Bishops’ Bible Illustrations - Aston, Margaret (Studies in church history, 1992)
The illustrations in the Bishops’ Bible have received more attention from art historians than from historians, though their story—which turns out to have been remarkably complicated—calls for the skills of both disciplines. The tale, which I can only outline here, throws interesting light on the state of the arts and art censorship in the early Elizabethan Church, at a time when there was much interrelationship between England and continental artists and craftsmen.